(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Production of vegetables under agroforestry system says that it is a good alternative especially under limited resources. This study was undertaken to find out the possibility of growing pea with highly adaptable two tree species; the Egyptian river hemp (Sesbania sesban) and white lead tree (Leucaena leucocephala) under two levels of nitrogen fertilizer. The results indicated that plant fresh and dry weights of pea were significantly affected with alley cropping treatments. Moreover, pea allied with Sesbania+1/2 recommended dose (RD) of N produced the heaviest plant fresh and dry weight. While, sole pea plants inoculated with Rhizobium treatment followed by pea allied with Sesbania+1/2 RD gave the highest number of main branches. Alley cropping system with Sesbania or Leucaena+1/2RD showed the best result for the total nitrogen %. Treatment with Rhizobium followed by growing with Sesbania+1/2 RD produced the highest N uptake values. On the other hand, pea with Sesbania+1/2 RD gave the highest % of K uptake. For nodulation status, alley cropping system of pea with Sesbania and Leucaena plus half of nitrogen RD significantly increased the pea fresh and dry nodules weight as well as the number of nodules compared to the other treatments. Thus, it appears that alley cropping system has great benefits on peas but still moderate N fertilization is the key factor in defining the productivity and sustainability of the production in Aswan, Egypt.